Models of educational intervention for people with ASD - Harris, Sandra (Henry Stewart Talks, 2010)
A multitude of models, Theoretical perspective, Empirical support, National Research Council, Advantages and disadvantages of models, Home-based models, Family, child, parent and sibling impact of home-based models, School based models, Center based models, Home based programs, Lovaas study and follow-up, School/center based, Naturalistic approaches, The Early Start Denver model, TEACCH model